Cellulase system of a free-living, mesophilic clostridium (strain C7). - Cavedon, K (1990)
The enzymatic activity responsible for crystalline cellulose degradation (Avicelase activity) by a mesophilic clostridium (strain C7) was present in culture supernatant fluid but was not detected in significant amounts in association with whole cells or in disrupted cells. Cells of the mesophilic clostridium lacked cellulosome clusters on their surface and did not adhere to cellulose fibers. The extracellular cellulase system of the mesophilic clostridium was fractionated by Sephracryl S-300 gel filtration, and the fractions were assayed for Avicelase and carboxymethylcellulase activities. The Avicelase activity coincided with an A280 peak that eluted in the 700,000-Mr region. Nondenaturing polyacrylamide gel electrophoresis and sodium dodecyl sulfate-polyacrylamide gel electrophoretic analysis of the 700,000-Mr fractions showed that Avicelase was present as a multiprotein aggregate that lost the ability to hydrolyze crystalline cellulose when partially dissociated by sodium dodecyl sulfate treatment. Proteins resulting from the partial dissociation of the aggregate retained carboxymethylcellulase activity. An Avicelase-deficient mutant of strain C7 (strain LS), which was not capable of degrading crystalline cellulose, lacked the Avicelase-active 700,000-Mr peak. The results indicated that an extracellular 700,000-Mr multiprotein complex, consisting of at least 15 proteins, is utilized by the mesophilic clostridium for the hydrolysis of crystalline cellulose. At least six different endo-1,4-beta-glucanases may be part of the cellulase system of strain C7. Sephacryl S-300 column fractions, corresponding to an A280 peak in the 130,000-Mr region, contained carboxymethylcellulase-active proteins that may serve as precursors for the assembly of the Avicelase-active complex by the mesophilic clostridium.